Dietary functional benefits of Bartlett and Starkrimson pears for potential management of hyperglycemia, hypertension and ulcer bacteria Helicobacter pylori while supporting beneficial probiotic bacterial response. (March 2015) - Sarkar, Dipayan; Ankolekar, Chandrakant; Pinto, Marcia; Shetty, Kalidas
Abstract: Phenolic-linked health benefits of Bartlett and Starkrimson pear cultivars were investigated for the potential relevance in managing type 2 diabetes and hypertension using in vitro enzyme models. Further effects of fermented (0, 24, 48, and 72-h with Lactobacillus helveticus ) pear juice on inhibition of Helicobacter pylori and proliferation of probiotic Bifidobacterium longum were also evaluated. High total phenolic content along with high 2, 2 diphenyl-1-picrylhydrazyl-linked free radical scavenging antioxidant activities were observed in peel extracts of both cultivars. In vitro enzyme assays with peel and pulp extracts also indicated high inhibitory activity of α-glucosidase and α-amylase used as models for anti-hyperglycemia benefits. Only the aqueous pulp extract of Bartlett pear had angiotensin I-converting enzyme inhibitory activity used as model for anti-hypertension benefits. Fermented acidic pH samples of both cultivars showed H. pylori inhibition at 48 and 72 h, while fermented sample of Starkrimson even showed inhibition at 24 h. Both cultivar extracts did not inhibit growth of probiotic B. longum . Highlights: Pear has potential for phenolic-linked management of type 2 diabetes associated hyperglycemia and hypertension. Fermented pear juices also possess inhibitory activity of stomach ulcer relevant bacterium Helicobacter pylori. Pear cultivars have relevance to be included in dietary strategies for better management of early stage hyperglycemia. This in vitro study provides conceptual foundation for animal and clinical studies involving pear to combat type 2 diabetes.